2016
DOI: 10.1007/s00417-016-3310-5
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy in patients with uveal melanoma after proton beam therapy

Abstract: Trabeculectomy is an option in intractable glaucoma in patients with uveal melanoma after proton beam therapy in single cases. Secondary interventions are common. Inoculation metastases are possible. Secure local tumor control must be a prerequisite for filtrating operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
(33 reference statements)
0
11
0
Order By: Relevance
“… 17 Successful treatment of these tumors prior to filtering surgery may reduce the likelihood of extrascleral spread and systemic metastases in the short term. 18 , 19 Though little data is available on long-term risk, present data suggests that the risk of extrascleral spread, systemic metastasis, and death does increase with time ( Table 1 ), even with treatment of the tumor. 15 , 18 In a pediatric patient with a life expectancy of several decades, the life-time risk of metastasis and premature death, even after treatment of the melanoma, must be weighed with appropriate gravity.…”
Section: Discussionmentioning
confidence: 77%
“… 17 Successful treatment of these tumors prior to filtering surgery may reduce the likelihood of extrascleral spread and systemic metastases in the short term. 18 , 19 Though little data is available on long-term risk, present data suggests that the risk of extrascleral spread, systemic metastasis, and death does increase with time ( Table 1 ), even with treatment of the tumor. 15 , 18 In a pediatric patient with a life expectancy of several decades, the life-time risk of metastasis and premature death, even after treatment of the melanoma, must be weighed with appropriate gravity.…”
Section: Discussionmentioning
confidence: 77%
“…However, our data support the assumption that in cases in whom the primary tumor has been definitively treated (i.e., eyes with no evidence of tumor growth at the time of GDD placement), the risk to the patient following invasive glaucoma surgery is not greater than clinical risk factors, namely tumor size and molecular prognostic profile, would suggest. Treatment of glaucoma in eyes with intraocular tumors, which is often caused by multiple mechanisms (incidence rate of 15.3% [Kim et al, manuscript under revision]) [1, 3, 28], may be challenging, and medical therapy, laser trabeculoplasty, and cyclophotocoagulation may not lead to adequate IOP control [11, 29, 30]. Cyclophotocoagulation is a treatment that may result in eventual phthisis if repeated more than once; therefore, offering cyclophotocoagulation may be minimally better than enucleation for ocular preservation [31].…”
Section: Discussionmentioning
confidence: 99%
“…The success rate in our study sample was comparable to that of the above study (80%) after 1 year. Riechardt et al [11] reported on the outcomes of trabeculectomy in 15 patients with uveal melanoma treated with proton beam radiation therapy. Two out of 15 patients were diagnosed with local treatment failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations